Actor Relationship Model in the Development of New Housing Facilities in Palangka Raya City: Problems and Urgency of Providing Public and Social Facilities - Riyanti, Nova; Jariah, Ainun; Ariyadi, Ariyadi; Selawaty, Desy (Universitas Medan Area, 2023)
This research aims to investigate the actor relationship model in fulfilling the obligation to provide public and social facilities by developers to the Palangka Raya City government. In addition, this research designs collaboration between actors in the sustainable management of public and social facilities by the Palangka Raya City government. The focus of the problem is on the rapid development of new housing construction in Palangka Raya City which has caused residential growth in various areas. Housing construction carried out by developers must meet infrastructure, infrastructure and utilities as basic needs in a residential environment. However, many new housing developments still do not provide public and social facilities as expected. Meanwhile, it is the obligation of every developer to provide land and hand it over to the Palangka Raya City government. In overcoming this problem, this research refers to the concept of a multiple factor approach (Sudiadi, 2015; Syaifudin & Astrika, 2016). Data was collected through observation, interviews and documentation in 2 sub-districts and 16 sub-districts, and analyzed qualitatively. This study concludes that the lack of relationship between actors/stakeholders is caused by the absence of regulations or regional regulations issued by the Regional Government. It was also found that housing development exceeded needs and did not provide adequate public and social facilities.